Design and Implement of Commodity Client Electronic Trading System - Qi, Chang Xing (Applied Mechanics and Materials, 2014)
According to the characteristics and requirements of the commodities Client Electronic trading system, This paper designed an commodity client electronic trading system. At the same time. According to TCP communication protocol, comprehensive using JSON and related technology,develops a communication program which used to connect to server. Further more, the communication protocol, loading balancing strategy,improving the efficiency of the communication methods are expounded in detail.